2013
DOI: 10.1002/jor.22321
|View full text |Cite
|
Sign up to set email alerts
|

MMP‐1 promoter polymorphism is associated with primary tendinopathy of the posterior tibial tendon

Abstract: Posterior tibial tendon (PTT) dysfunction is recognized as an etiology leading to acquired flatfoot in adults, causing significant functional loss. Many risk factors and systemic conditions have been proposed in literature. However, many patients present PTT dysfunction without any of these characteristics. This suggests that there could be a genetic influence associated with posterior tibial tendinopathy. The purpose of the present study is to investigate the association of the À1607 polymorphism in the promo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
9

Year Published

2014
2014
2016
2016

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 30 publications
0
29
0
9
Order By: Relevance
“…In other studies from our research group, we showed that MMP‐1 g.‐1607 G > GG (rs1799750) and MMP‐8 g.‐799 C > T (rs11225395) polymorphisms were also associated with tendinopathy in PTT ( p < 0.001) in a group of 150 volunteers . In the present study, which used part of the same population, the MMP‐13 g.‐77 A > G (rs2252070) polymorphism was included in the roll of MMPs associated with PTT polymorphisms (Table ).…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…In other studies from our research group, we showed that MMP‐1 g.‐1607 G > GG (rs1799750) and MMP‐8 g.‐799 C > T (rs11225395) polymorphisms were also associated with tendinopathy in PTT ( p < 0.001) in a group of 150 volunteers . In the present study, which used part of the same population, the MMP‐13 g.‐77 A > G (rs2252070) polymorphism was included in the roll of MMPs associated with PTT polymorphisms (Table ).…”
Section: Resultsmentioning
confidence: 96%
“…In the previous analysis of the genetic influence in posterior tibial tendinopathy, we concluded that MMP‐8 g.‐799 C > T (rs11225395) and MMP‐1 g.‐1607 G > GG (rs1799750) polymorphisms are associated with a PTT dysfunction. We have confirmed our results in an expanded sample.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[9] PTTD is more frequent in hypertensive, obese, and rheumatic patients with peak incidence at the age of fifties; in addition, it is 3 times more common in females. [10] In our case, hypertension, rheumatoid arthritis, and overweight were considered as adverse factors in the development of PTTD. PTTD results in structural destabilization of the mid- and hindfoot.…”
Section: Discussionmentioning
confidence: 93%